EFEKTIVITAS WORKSHOP ACADEMIC WRITING UNTUK MENINGKATKAN REGULASI DIRI DALAM BELAJAR - Mahkamah Brantasari (SISTEMA: Jurnal Pendidikan, 2022)
Students in completing their studies will have an obligation to complete their final assignment, either in the form of a thesis or an article. Writing is an activity that cannot be avoided by students because writing is part of the many tasks that students will complete. As for what is meant by an idea, namely the opinion, experience and knowledge of the author. Either obtained in the past from his own experience, or in the present through literature review. The Academic Writing Workshop will be held with the aim of improving students' writing skills in thesis and scientific journals. It is hoped that this activity will make it easier for students of the Pg Paud UWGM Samarinda Study Program to put their ideas and thoughts into writing. In this study using a quasi-experimental method, this method was used because in reality it was difficult to get a control group used in the study. Not all variables and experimental conditions can be tightly regulated and controlled. The pretest was given before the workshop was held, the results of the analysis of student self-regulation questionnaire data obtained the highest score of 119 and the lowest score of 90 with a range of values ​​of 29, mean 106.69, standard deviation 6993. In the posttest given after the workshop was carried out, the highest score was 122 and the lowest score was 93, with a range of values ​​29, mean 107.61, standard deviation 7.068. This research was conducted in 3 meetings in the same group. The population of this research is Pg Paud Uwgm Samarinda students who will carry out their final assignment on the UWGM Samarinda campus.